Fractionation of baker's yeast vinasse via ultrafiltration: assessment of feasibility. (26th December 2018) - Vukušić, Josipa Lisičar; Millenautzki, Thomas; Sedaghati, Masoud; Schallenberg, Marc; Müller, Peter; Hof, Jendrik; Mösche, Marek; Barbe, Stéphan
Summary: The potential of vinasse, gained from baker′s yeast production for the recovery of valuable molecules (invertase, food grade proteins and betaine), has been assessed. Particularly natural betaine, a trimethyl derivative of glycine, attracts more and more attention in human and animal nutrition. In this work, a straightforward membrane‐based process for the recovery of natural betaine and a very promising betaine‐rich protein fraction from fermentation broth of baker′s yeast was developed. The difficult separation of external invertase from yeast cells was observed in this work. Anyway, a residual invertase activity was found in vinasse, but it could not be efficiently purified to generate an industrial‐strength product. The presented process can be easily implemented in a conventional baker's yeast production plant by integrating an ultrafiltration station and an adsorption system. Based on our calculations, a potential recovery up to 1486 t year −1 of betaine‐rich proteins (5 € kg −1 ) and 593 t year −1 Betafin ® similar natural betaine (6–7 € kg −1 ) may be achieved. Abstract : A straightforward process for the simultaneous recovery of invertase, natural betaine and a betaine rich protein fraction from baker's yeast vinasse.